Respon Kelompok IRT Atas Dampak Covid-19 Melalui Inovasi Desain Kemasarn Dan Strategi Digitalisasi Marketing - Adam Adam; Isnaini Isnaini; Hery Syahrial; Sunaryo Sunaryo; Miftahuddin Miftahuddin (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
This community service  activity is in response to the situation of the covid19 pandemic and the all-digital industrial era 4.0. Circumstances that have disrupted every business unit both large and small. This reality makes small businesses must be able to adapt to these new changes. Activities in the form of mentoring involve a group of business partners of housewives in Namorambe Village deli serdang regency. The goal is to participate in helping the economic empowerment of the community to survive and further develop. The types of assistance include; a) coaching and education in the field of business management, b) training and mentoring product packaging innovations(packaging), c) training and mentoring marketing management. Target partner activities have been able to develop and practice what has been socialized by the companion team.Keywords: Mentoring, Product Innovation, Marketing Strategy